Differences in cytokine levels between Extrinsic and Intrinsic Atopic Dermatitis (Journal of the College of Basic Education, 2022)
Atopic dermatitis (AD) is a common inflammatory skin disease characterized by several clinical , immunological and biochemical alterations . Comparing the patients with Extrinsic and Intrinsic forms of AD, we investigate the role of immunological markers in the pathogenesis of AD. Serum concentrations of IL-12, IL-13, IL-18 and IgE were measured using ELISA method and severity was detected by a special scoring system (SCORAD Index). Serum IgE and IL-13 concentrations were both elevated in the EAD group compared to IAD and control group, whereas, serum IL-12 and IL-18 concentrations were decreased in EAD group compared to IAD and control group, this may suggest a specific cytokine profile involved in each form of AD which need further investigation.